Mechanical properties of bundled carbon nanoscroll - Huang, Jie (2018)
The self-rolling process of single-layer graphene around a core SWCNT leads to the formation of a spiral structure – a carbon nanoscroll (CNS), which is topologically open with two slippery free edges along its axial direction. By using molecular dynamics simulations, the mechanical properties of single CNS were studied. In addition, three individual single CNS samples were put together as a bundle to study the effect of bundling on the mechanical properties. Since CNS exhibits open slippery edges, three different configurations of bundled CNS were simulated to investigate the effect of the orientation of the slippery edges on the mechanical properties as well. We found that bundled CNS is capable of resisting approximately three times the external tensile loading compared to their single counterpart although they fail at the same strain. Additionally, upon compression, the bundled CNS buckled at a slightly lower critical strain with an ultimate strength almost three times that of single sample. Torsional properties have also been investigated. The simulation results showed that the bundled CNS failed at a smaller twisted angle per unit length with a much higher ultimate torque compared to the single CNS. Last but not least, we found the orientation of the slippery edges of the bundled CNS sample exhibits negligible influence on the mechanical properties.